Shock-wave induced compressive stress on alumina ceramics by laser peening - Pratik Shukla; Robert Crookes; Houzheng Wu (Materials & Design, 2019)
Laser shock peening (LSP) of Al2O3 advanced ceramics is reported, showing underpinned physical mechanisms and potential benefits. It is known that localised plastic deformation can be induced in ceramics in the presence of a high hydrostatic pressure. It is therefore of high interest to apply LSP on large surface areas on ceramics in order to create a strengthening mechanism. An Nd: YAG laser was used for the study at an increment of 1 J, 1.5 J and 1.7 J laser energy. The LSP surface treatment was characterized using a 3-D surface profiler and a Cr3+ fluorescence spectroscopy from which residual stress and dislocation densities were determined after mapping with acquired Cr3+ fluorescence spectra. The results showed an increase in roughness by 10% at 1 J, to 62% at 1.5 J, and 95% at 1.7 J of laser energy. The net compressive stress increased from 104 MPa at 1 J, to 138 MPa at 1.5 J and 168 MPa at 1.7 J. The highest dislocation density was 2.0 × 1014 1/m2 and an average of 2.1 × 1013 1/m2 within the low compression zone at 1.5 J of laser energy. These results have shown a way forward to not only generate local plastic deformation, but open up a new avenue towards strengthening ceramics using laser peening technology. Keywords: Laser shock peening: ceramics, Residual stress, Compression, Plasticity